2021
DOI: 10.1093/cdn/nzab051_027
|View full text |Cite
|
Sign up to set email alerts
|

Babybyte: Usability Testing of a mHealth App Prototype to Improve Responsive Feeding Practices in Parents of Infants and Toddlers

Abstract: Objectives With the recent addition of nutrition guidance for children under the age of 2 years to the 2020 Dietary Guidelines, new strategies are needed to communicate reputable feeding information to parents of infants and toddlers for optimal nutrition and prevention of early childhood obesity. The objective of this study was to determine usability of a mHealth app prototype (BabyByte) containing early childhood feeding guidance based on recommended responsive feeding practices for parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We followed best practices and used a guided approach (with therapists and parent coaches). In terms of acceptability, the MAUQ findings in the current study indicated slightly lower usability than those for a similar App prototype which targeted parent feeding practices with their infants and toddlers (71). Although engagement and attrition in the BEAM program was comparable to other digital interventions that target parent mental health, parenting skills, or child behavior (25), the lower rate of retention in the intervention compared to the control group may suggest program feasibility issues.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We followed best practices and used a guided approach (with therapists and parent coaches). In terms of acceptability, the MAUQ findings in the current study indicated slightly lower usability than those for a similar App prototype which targeted parent feeding practices with their infants and toddlers (71). Although engagement and attrition in the BEAM program was comparable to other digital interventions that target parent mental health, parenting skills, or child behavior (25), the lower rate of retention in the intervention compared to the control group may suggest program feasibility issues.…”
Section: Discussionmentioning
confidence: 55%
“…This may reflect miscommunications given terminology can differ between researchers and tech developers. Before data collection begins, it is important to determine what variables are needed (70,71), translate them into events that can be tracked, and check whether they are tracked as automatically collected events in Google Analytics (e.g., total time spent on the App, session start) or need to be implemented as custom events during App development (e.g., time spent on different App screens, tracking when video content is started, paused, resumed, watched completely). This should be done as early as possible during App development as some early decisions can affect the custom events that can be collected (e.g., the choice of video player used in App development determines whether the number of minutes a video is watched can be tracked).…”
Section: Data Trackingmentioning
confidence: 99%
“…Quantitative feedback using the MAUQ was broadly very positive, indicating high levels of usability and satisfaction among responders [ 46 ]. The MAUQ has been recently introduced and so has not yet gained widespread uptake; however, HeadOn has similar levels of usability compared with other digital interventions in the literature, including those targeting childhood feeding and pediatric burns [ 58 , 59 ]. The qualitative interviews also highlighted some important areas for refinement, including increasing the number of notifications, adding a remove unit function to the alcohol tracker, and altering the language used in the thought monitor.…”
Section: Discussionmentioning
confidence: 99%